Effects of ticagrelor monotherapy vs. clopidogrel monotherapy on platelet reactivity: a randomized, crossover clinical study (SINGLE study). (17th November 2022) - He, Meijiao; Yan, Wei; Zhang, Yun; Kong, Yihui; Han, Xuejie; Ren, Jie; Zhao, Zhongyang; Liu, Guangzhong; Shi, Jing; Li, Yue
Abstract: Increasing clinical trials demonstrated that the discontinuation of aspirin while maintaining a P2Y12 inhibitor monotherapy could decrease the risk of bleeding without losing the antithrombotic effect. However, no data are available on the platelet reactivity of patients undergoing ticagrelor monotherapy vs. clopidogrel. Therefore, we performed this study to observe the efficacy of ticagrelor monotherapy vs. clopidogrel in Chinese patients with chronic coronary syndrome. This randomized, single-blinded, crossover trial enrolled 50 patients who were administered with ticagrelor (90 mg twice daily for 2 weeks) or clopidogrel (75 mg once daily for 2 weeks). Followed by a 2-week washout period, the two groups of patients underwent a crossover trial. Light transmission aggregometry (LTA) and thromboelastography (TEG) assays were used to test platelet reactivity. The platelet aggregation rate (PAgR) of ADP and AA was significantly lower with ticagrelor than clopidogrel (PAgR of ADP, 27.30% (7.30%-42.635%) vs. 35.55% (12.03%-69.25%), P = .0254; PAgR of AA, 77.80% (21.60%-86.43%) vs. 83.10% (67.13%-87.20%), P = .0400). There was no significant difference in PAgR of collagen and epinephrine between the two groups. The TEG assay showed that ADP and AA, which induced the inhibition of platelet aggregation, were significantly higher in the ticagrelor group than those in the clopidogrel group [ADP%, 69.00% (59.68%–88.95%) vs. 60.55% (35.98%–78.35%), P = .0020; AA%, 53.65% (22.75%–79.28%) vs. 15.15% (5.75%–70.25%), P = .0127]. High on-treatment platelet reactivity (HTPR) on ADP was 2.17% with ticagrelor and 19.57% with clopidogrel. HTPR on AA was 50.00% with ticagrelor and 69.57% with clopidogrel. Ticagrelor and clopidogrel caused the inhibition of ADP and AA-induced platelet aggregation. Moreover, ticagrelor monotherapy had a stronger inhibitory effect than clopidogrel monotherapy (except on collagen and epinephrine).